The Role of Vitamin K in Neurodegenerative Disorders: Mechanisms, Evidence, and Therapeutic Potential - Bajaj, Avik (Journal of Neonatal Surgery, 2025)
Neurodegenerative disorders, including Alzheimer's disease (AD), Parkinson's disease (PD), and Multiple Sclerosis (MS), pose significant public health challenges worldwide. Emerging evidence suggests that Vitamin K, a fat-soluble vitamin traditionally known for its role in blood coagulation, also has neuroprotective properties. This review explores the role of Vitamin K in neurodegeneration, focusing on its antioxidant, anti-inflammatory, and neuroprotective functions. It also evaluates the clinical and experimental evidence that support the potential of Vitamin K as a therapeutic agent for neurodegenerative disorders. The paper highlights the need for further research to elucidate the precise mechanisms of Vitamin K in brain health and its translational application in neurodegenerative conditions